Korelasi persepsi tentang efek samping kemoterapi dengan kualitas hidup pasien kanker payudara - Shanti Lesmana Sari; Rani Lisa Indra; Raja Fitriana Lestari (Universitas Ahmad Dahlan, 2019)
Chemotherapy treatments undergone by breast cancer patients have several side effects. From the side effects that, each patient perceives the side effects that will interfere with their daily lives which in turn affect the quality of life. This research was made for showing the correlation of chemotherapy side effects with the quality of life of breast cancer patients in Arifin Achmad Hospital in Riau Province. The research was one of quantitative correlation research with a cross-section method that had been done to 63 respondents in Arifin Achmad Hospital in Riau Province by using consecutive sampling technique bye used was questionnaire. The test used an unpaired t-test. This research result was gotten if Pvalue=0.216 (Pvalue=0.05), which mean is no correlation between chemotherapy side effect perspective and quality of life of breast cancer patients. Based on the result, we hope Arifin Achmad Hospital in Riau Province develop more health service to the community to increase positive judgement from chemotherapy treatment and quality of life of breast cancer patients.